Advertisement Remove all ads

If F: R → R is Defined by F(X) = X2 − 3x + 2, Find F(F(X)). - Mathematics

If f→ R is defined by f(x) = x2 − 3+ 2, find f(f(x)).

Advertisement Remove all ads

Solution

It is given that fR → R is defined as f(x) = x2 − 3x + 2.

`f(f(x)) = f(x^2 - 3x + 2)`

`= (x^2 +3x + 2)^2 - 3(x^2 - 3x + 2) + 2`

= `x^4 + 9x^2 + 4 - 6x^2 - 12x + 4x^2 - 3x^2 + 9x  -  6 + 2`

`= x^4 - 6x^2 + 10x^2 - 3x`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 12 Maths
Chapter 1 Relations and Functions
Q 3 | Page 29
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×